Exploring the physical properties of lensed star-forming clumps at 2 ≲ z ≲ 6. Issue 3 (18th August 2022) - Meštrić, U; Vanzella, E; Zanella, A; Castellano, M; Calura, F; Rosati, P; Bergamini, P; Mercurio, A; Meneghetti, M; Grillo, C; Caminha, G B; Nonino, M; et al.
ABSTRACT: We study the physical properties (size, stellar mass, luminosity, and star formation rate) and scaling relations for a sample of 166 star-forming clumps with redshift z ∼ 2–6.2. They are magnified by the Hubble Frontier Field galaxy cluster MACS J0416 and have robust lensing magnification (2 ≲ μ ≲ 82) computed by using our high-precision lens model, based on 182 multiple images. Our sample extends by ∼3 times the number of spectroscopically confirmed lensed clumps at z ≳ 2. We identify clumps in ultraviolet continuum images and find that, whenever the effective spatial resolution (enhanced by gravitational lensing) increases, they fragment into smaller entities, likely reflecting the hierarchically organized nature of star formation. Kpc-scale clumps, most commonly observed in field, are not found in our sample. The physical properties of our sample extend the parameter space typically probed by z ≳ 1 field observations and simulations, by populating the low mass ( M ⋆ ≲ 10 7 M⊙ ), low star formation rate (SFR ≲ 0.5 M⊙ yr −1 ), and small size ( R eff ≲ 100 pc) regime. The new domain probed by our study approaches the regime of compact stellar complexes and star clusters. In the mass–size plane, our sample spans the region between galaxies and globular clusters, with a few clumps in the region populated by young star clusters and globular clusters. For the bulk of our sample, we measure star formation rates which are higher than those observed locally in compact stellar systems, indicating different conditions for star formation at high redshift than in the local Universe.